The effects of implementing the flipped class model on non-English majored students’ writing performance - Bich Nhu Ho; Van Loi Nguyen; Phuong Thao Bui; Van Thong Nguyen; Trung Cang Nguyen (CTU Journal of Innovation and Sustainable Development)
Education is continuously evolving and adapting to meet the diverse learning needs of students. A significant innovation in this field is the flipped class model, a pedagogical approach that redefines the traditional classroom structure. This creative approach seeks to enhance student-centred learning by combining in-class discussion with pre-class video instruction. This paper aims to investigate its effects on undergraduate students' writing performance. In this study, the flipped model was implemented to teach writing lessons, aligning sessions with Bloom's Taxonomy. A quasi-experimental design was employed with two groups of eighty non-English major students at a university in the Mekong Delta, South Viet Nam. The experimental group was exposed to the flipped model, while the control group received conventional writing instruction. The treatment consisted of six 50-minute writing sessions. Results show that students in the experimental group achieved higher mean scores compared to their counterparts in the control group. This finding highlights the effects of the flipped classroom technique in enhancing writing proficiency. Pedagogical implications are suggested for teaching writing to learners who study English as a foreign language.